2016
DOI: 10.1093/cid/ciw845
|View full text |Cite
|
Sign up to set email alerts
|

Impact and cost-effectiveness of selective human papillomavirus vaccination of men who have sex with men

Abstract: SummaryOffering human papillomavirus (HPV) vaccination to men who have sex with men up to age 40 years via genitourinary clinics will have a large impact on HPV-related diseases and is likely to be cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 41 publications
(38 reference statements)
1
60
0
1
Order By: Relevance
“…HPV-6 and 11 types, which can cause genital warts [4,22], were the most prevalent low-risk HPV types among MSM attending university, and these two types could be protected by both the four-valent and nine-valent HPV vaccines. A previous study found that HPV vaccinations in males were highly effective in largely preventing anogenital warts and anal cancers [23]. The modeling analysis predicted that a vaccination program for males only with a certain coverage (80%) could achieve a reduction of 90% in HPV infections in MSM.…”
Section: Discussionmentioning
confidence: 95%
“…HPV-6 and 11 types, which can cause genital warts [4,22], were the most prevalent low-risk HPV types among MSM attending university, and these two types could be protected by both the four-valent and nine-valent HPV vaccines. A previous study found that HPV vaccinations in males were highly effective in largely preventing anogenital warts and anal cancers [23]. The modeling analysis predicted that a vaccination program for males only with a certain coverage (80%) could achieve a reduction of 90% in HPV infections in MSM.…”
Section: Discussionmentioning
confidence: 95%
“…Since 2011, the Advisory Committee on Immunization Practice (ACIP) recommended routine vaccination for all males at ages 11‐12 years, through age 21 years for men not previously fully vaccinated, and through age 26 years for MSM and immunocompromised men, including those with HIV infection . Quadrivalent HPV vaccination of MSM was likely reported as an effective and cost‐effective way for reducing the burden of HPV‐related disease in MSM . Particularly, both clinical and economic benefits were reported for quadrivalent HPV vaccine in HIV‐negative MSM as adjunct strategy in the prevention of recurrent high‐grade intraepithelial neoplasia, decreasing the lifetime risk of anal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] Quadrivalent HPV vaccination of MSM was likely reported as an effective and cost-effective way for reducing the burden of HPV-related disease in MSM. 39,40 Particularly Current evidences support to achieve the target of universal vaccination with a gender-neutral approach by considering both HPV vaccination's clinical effectiveness and economic sustainability. 42,43 Therefore, as MSM should not benefit-even indirectly-from an increasing coverage among females, they represent an important at risk group population to monitor, in which the implementation and the evaluation of effective immunization programmes is required, as well as an increased promotion of knowledge and awareness on HPV prevention among vaccine providers, subjects receiving vaccine and their relatives.…”
Section: Genotype Distribution In Hpv Positive Msmmentioning
confidence: 99%
“…These data have been used to inform the likely cost-effectiveness and the design of the HPV-MSM programme 8. As this programme implementation starts, GUMCAD data will be well placed to monitor attendances (including potential additional attendances attracted by HPV vaccination), vaccine uptake and course completion.…”
Section: Discussionmentioning
confidence: 99%